2019
DOI: 10.1039/c9bm01190k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumour effect for hepatocellular carcinoma in the advanced stage using a cyclodextrin-sorafenib-chaperoned inclusion complex

Abstract: We have proposed and classified the HCC tumor of HCC tumor-bearing BALB/c nude mice to four stages. Cyclodextrin-sorafenib-chaperoned inclusion complexes were prepared and applied to treat advanced HCC tumor-bearing mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Tumor microvessel density (MVD) is a marker that can be used to evaluate tumor angiogenesis. For instance, cluster designation 34 (CD34) staining has been used to evaluate the growth of neovascularization in HepG2 xenograft tumor-bearing mice (10), and CD31 staining can be used to identify the stages of HCC (11). Other research has shown that CD105 staining is useful in quantifying the formation of new microvessels in HCC (12).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor microvessel density (MVD) is a marker that can be used to evaluate tumor angiogenesis. For instance, cluster designation 34 (CD34) staining has been used to evaluate the growth of neovascularization in HepG2 xenograft tumor-bearing mice (10), and CD31 staining can be used to identify the stages of HCC (11). Other research has shown that CD105 staining is useful in quantifying the formation of new microvessels in HCC (12).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the covalent functionalization, the capability of pristine CDs as hosts to encapsulate a large number of organic species forms the basis of many practical applications in the pharmaceutical formulation [ 19 , 20 , 23 , 24 ], cosmetics [ 25 ], environmental remediation [ 26 , 27 , 28 ], agriculture, and food industry [ 29 ]. This originates from the unique hydrophobic inner cavity and hydrophilic outer space of CDs, with the latter also critical for imparting solubility to the otherwise less soluble organic species via inclusion [ 1 , 30 , 31 ]. These encapsulated species can be subsequently released on-demand with external stimuli, such as competitive solvent association, light-/heat-triggered conformation switch, and chemical stimuli (e.g., redox reactions) [ 19 , 20 , 23 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intrigued by these highly favorable traits of CDs, a huge body of work has been done toward the efficient hierarchical catch-release systems through facile host–guest hybridization to harness the beneficial properties of both CDs and the guests [ 23 , 31 , 32 , 36 , 37 ]. The most widely studied host and guest pair feature β-CD and adamantane derivatives mainly due to their wide availability and good size match [ 23 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 However, many previous sfb nanoformulations were studied in immunedeficient mice, and few studies have been performed on immune-competent mice, especially on the HCC tumor model. 16,22,23 Thus, little is known about the relationship between its immunostimulatory effect on immune cells and its therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%